(untitled) (Teología, 2016)
Mario de FranÁ§a Miranda proposes in his article to take account of the theological importance of caring for our common home. Forgetting the importance of treating nature with respect, springs from a crisis rooted in a loss of meaning in the plan of salvation that has been pronounced upon man. A plan that embraces the whole cosmos.